Research and Design Incubator to Control Temperature the Egg Back Automatically - ลือมาสือนิ, อัสม๊ะ; สมานพิทักษ์, ลตีฟา; กาซอ, ซุลกิพลี (YRU Journal of Science and Technology, 2018)
This research aims to study and design a controlled temperature to hatch eggs and egg back automatically. To increase the incidence of chicken to incubate for a period of 21 days from the conditioned to hatch eggs and egg back automatically.The results showed that designed and built temperature controlled automatic egg to hatch eggs in return. The size 53x63x83 cm incubators thickness 10 mm insulation (foam) insulation in between two sheets of plywood. Install automatic climate control and return the egg. The hole on the left side bottom right and a fan for ventilation. Heating inside the enclosure by installing lighting and humidity inside the cabinet by installing a smoke machine. The test temperature controlled to incubate an egg to automatically measure the temperature every five hours, the temperature inside the eggs hatch-back with automatic averaging at the right temperature. 37.5 ºC ambient temperature There are similar every moment in between 30 to 31.7 ºC and the relative humidity is the same all the time in between 50.76% to 53.24%.